bZIP edgetic mutations: at the frontier of plant metabolism, development and stress trade-off - Lorenzo, Oscar (J Exp Bot, 2019)
This article comments on: Garg A, Kirchler T, Fillinger S, Wanke F, Stadelhofer B, Stahl M, Chaban C. 2019. Targeted manipulation of bZIP53 DNA-binding properties influences Arabidopsis metabolism and growth. Journal of Experimental Botany 70, 5659–5671.